An Error Analysis In Changing Active Voice Into Passive Voice Of Simple Past Tense At Twelfth Grade Students Of SMAN 8 Mandau - Maya Sari, Harum (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2023)
This research aimed to analyze an error analysis in changing active voice into passive voice of simple past tense at twelfth grade students of SMAN 8 Mandau. Specially, it aimed to obtaining and identifying the common error in using passive voice in simple past tense. The data sources of this research were 30 students of twelfth grade of SMAN 8 Mandau which were taken by cluster random sampling. The writer used the descriptive quantitative in this research to describe students’ errors and analyzed the data. The data were taken from the test. the findings showed that there were 214 errors made by students. it can be classified from the highest to the lowest: misformation (85 errors or 38%), omission (63 errors or 29%), misordering (50 errors or 24%) and addition (16 errors or 8%). the dominantly error made by students in changing active voice into passive voice of simple past tense was misformation that consist 85 errors or 38%.